Dehydroalanine and dehydrobutyrine in aging and cataractous lenses reveal site-specific consequences of spontaneous protein degradation - Paredes, Jessica; Wang, Zhen; Patel, Purvi; Rose, Kristie L.; Schey, Kevin L. (Frontiers in Ophthalmology, 2023)
Protein post-translational modifications (PTMs) have been associated with aging and agerelated diseases. PTMs are particularly impactful in long-lived proteins, such as those found in the ocular lens, because they accumulate with age. Two post-translational modifications that lead to protein-protein crosslinks in aged and cataractous lenses are dehydroalanine (DHA) and dehydrobutyrine (DHB); formed from cysteine/serine and threonine residues, respectively. The purpose of this study was to quantitate DHA and DHB in human lens proteins as a function of age and cataract status. Human lenses of various ages were divided into five donor groups: transparent lenses (18-22-year-old, 48-64-year-old, and 70-93-year-old) and cataractous human lenses of two age groups (48-64-year-old lenses, and 70-93-year-old lenses) and were subjected to proteomic analysis. Relative DHA and DHB peptide levels were quantified and compared to their non-modified peptide counterparts. For most lens proteins containing DHA or DHB, higher amounts of DHA-and DHB-modified peptides were detected in aged and cataractous lenses. DHA-containing peptides were classified into three groups based on abundance changes with age and cataract: those that (1) increased only in age-related nuclear cataract (ARNC), (2) increased in aged and cataractous lenses, and (3) decreased in aged lenses and ARNC. There was no indication that DHA or DHB levels were dependent on lens region. In most donor groups, proteins with DHA and DHB were more likely to be found among urea-insoluble proteins rather than among water-or urea-soluble proteins. DHA and DHB formation may induce structural effects that make proteins less soluble in water that leads to age-related protein insolubility and possibly aggregation and light scattering.